Conquering future worries: How positive thinking training helps students overcome anxiety - Yuniarti, Kwartarini Wahyu; Anggawijayanto, Erydani; Rinaldi, Martaria Rizky (Jurnal Ilmiah Psikologi Terapan, 2025)
Anxiety is a common occurrence among individuals facing transitions in life phases, including students who have certain hopes, goals, and standards of living related to their future. As they near the end of their studies, in addition to their final assignments, envisioning the future also becomes a source of anxiety for students. Anxiety is influenced by cognitive performance, especially the perception of things not yet experienced. Anxiety about the future is influenced by negative perceptions of things not yet experienced. One effective therapy in reducing this anxiety is positive thinking therapy. This study aims to prove the effect of positive thinking therapy on 17 male and female students aged between 20 – 24 years old. The participants were selected by purposive sampling method and obtained 17 participants. The 17 participants were randomly divided into two groups, as control and experimental groups. The experiments conducted with repeated measure control group design. The result of repeated measure from the experimental group showed F = 28.2, p < 0.01 and control group showed F = 46,1 and p < 0.01. Meanwhile, the results of independent sample t-test analysis showed a score of F = 2.25 with P < 0.05. The result showed that positive thinking therapy is capable to decrease the symptoms of future anxiety.